Relative Responsiveness of Trade Flows to a Change in Prices and Exchange Rate - (:unkn) unknown (My University, 2015)
This dissertation includes two essays in international trade. In my first essay I consider Orcutt’s (1950) hypothesis in which trade flows respond to changes in exchange rate more quickly than they do to changes in prices. There are several studies, which test the Orcutt’s hypothesis by imposing lag structure on both relative prices and exchange rate. I employ generalized impulse response analysis as an alternative approach to test Orcutt’s hypothesis using the sample of developed and developing countries. The empirical results do not support Orcutt’s hypothesis in most cases. In my second essay I investigate the effects of technological progress on the speed with which relative prices and exchange rate affect trade. I employ ARDL cointegration approach for two sub-samples (1973-1990 and 1991-2013) of selected developed and developing countries. The results illustrate that due to technological progress the lags of relative prices and exchange rate have been shortened during post 1990.
Keywords: Ardl Approach; Cointegration; Impulse Response; International Trade; Orcutt's Hypothesis; Trade Flows